Speech Production Errors In Microteaching Made By English Department Students Of Muhammadiyah University of Surakarta In 2014/2015 Academic Year - Utami, Etik Wahyu Tri; , Prof. Dr. Endang Fauziati, M. Hum; , Aryati Prasetyarini, S.Pd, M.Pd (2015)
This research is a descriptive qualitative research. Which aims to describe the types of errors, the frequency of errors, the dominant error, and to explain the source of error made by English Department Students in Microteaching class. In collecting data, the writer watches and listens to the video, writes the scripts of the videos, then identifies the data, and selects the data based on the types of error. The writer uses theory of Clark and Clark to analyze the speech error. Based on the data, the researcher finds 641 error utterances that consist of 512 utterances or 79, 86% of speech error, 58 utterances or 9, 04% of morphological error and 71 utterances or 11, 1% of syntactical error. The writer finds 103 utterances or 16,06% of silent pause, 217 utterances or 33,85% of filled pause, 142 utterances or 22,15% of repeats, 20 utterances or 3,12% of correction, 10 utterances or 1,56% of stutters, 7 utterances or 1,09% of unretraced false start, 13 utterances or 2,03% of retraced false start, 47 utterances or 7,33% of vocabulary error, 11 utterances or 1,71% of error in the choice of word, 43 utterances or 6,70% of omissions of bound morpheme -s, 5 utterances or 0,80% of omission to be, 5 utterances or 0,80% of addition of bound morpheme -ing, 7 utterances or 1,09% of addition of preposition, 4 utterances or 0,62% of addition of article, and 7 utterances of misuse to be. The dominant error is speech error especially filled pause. The writer finds two sources of error, namely cognitive and psychological reasons. Cognitive reasons relates to the speaker's difficulty to speak clearly. Then psychological reasons relates to particular conditions such as anxious, nervous, and in hurry. Keywords: speech production, speech error, grammatical error